New Evidence on the Relationship between Risk Attitudes and Self-Employment - Olga Skriabikova; Thomas Dohmen; Ben Kriechel (Institute for the Study of Labor (IZA), 2014)
This paper analyses the impact of risk attitudes on the decision to become self-employed among individuals who grew up under the communist regime in Ukraine, which banned self-employment so that individuals could not observe what it is like to be self-employed. Since the intra-family transmission of self-employment experiences was largely shut down, the observed correlation between risk preferences and self-employment after transition is unlikely to be driven by parents transmitting self-employment experience and risk preferences to their children. Robustness checks on a sample of East Germans confirm that such a third factor explanation is implausible, thus shedding light on the causal nature of the relation between risk preferences and the decision to become self-employed.
Keywords: J24; D81; P3; 330; self-employment; risk attitudes; intergenerational transmission of self-employment and risk attitudes; SOEP; ULMS